Android-based virtual laboratory with starter experiment approach for learning vertebrate organ systems in high school - Hasanah, Alfinatul; Risnasari, Medika (Universitas Negeri Yogyakarta, 2025)
Limited laboratory equipment causes practicum of vertebrate animal organ systems to be rarely carried out so that learning is only theoretical and has an impact on student understanding that is less than optimal. This study aims to develop and test the validity and feasibility of an Android-based virtual laboratory with a starter experiment approach on vertebrate animal organ system material for high schools. This media is also equipped with LKP (Practicum Worksheet) to support virtual laboratory activities. This research uses the Research and Development (R&D) method with the ADDIE model. Data were collected through validation questionnaires from media experts, material experts, and trials to students, then analyzed descriptively, quantitatively, and qualitatively. The validation results show that the virtual laboratory has a validity level of 91% from media experts and 89% from material experts, which is included in the